Screening the brain: molecular fingerprints of neural stem cells - Maurer, Martin H.; Kuschinsky, Wolfgang (Current stem cell research & therapy, 2006)
With the development of high-throughput technologies like microarrays for genomic and transcriptomic analysis, and two-dimensional gel electrophoresis, mas...